Perspectivas políticas comparadas de las noblezas europeas en la transición del XVI al XVII - Carrasco Martínez, Adolfo, 1964- (2003)
Este trabajo presenta las posibilidades que ofrece la comparación de los textos políticos surgidos en Europa en torno a 1600 para aclarar la posición de las diversas noblezas continentales. Desde finales del siglo XVI las relaciones político-sociales entraron en un proceso de transformación basado en la convicción de que la disyuntiva entre ser dominado o dominar constituía la única controversia relevante en torno al poder. Para las noblezas europeas, ello supuso un estrechamiento de su campo de operaciones con consecuencias no sólo prácticas, sino también relacionadas con la misma identidad de grupo e individual.
The article presents the prospectives of comparing the European political texts around 1600, in order to explain the political position of European nobilities. Since the end of the XVIth century, the sociopolitical relations entered into a transformational process based on the conviction that the alternative between being dominated or dominate constituted the only relevant controversy around the power. For the European nobilities, this new scene supposed a narrowing of their field of operations with not only practical consequences, but also those related to the same group and individual identity. Aspects like the definition of nobility, the protagonism... (Ver más) that touched to the aristocracy in the sociopolitical secene, or the relation with the kings and their administrative machine, were the object of an intense discussion in England, France or the Hispanic Monarchy. Therefore, a wide debate with political and ethical arguments took place, where the nobiity looked for justification and defense, returning their glance to the classic sources ¿some facets of the aristotelism and stoicism¿ that were performed according to the contemporary context.
Keywords: Nobleza; Política